Deglycosylation of epithelial cell adhesion molecule affects epithelial to mesenchymal transition in breast cancer cells. Issue 4 (24th September 2018) - Liu, Xue; Yang, Liu; Zhang, Dandan; Liu, Tingjiao; Yan, Qiu; Yang, Xuesong
Abstract: The transmembrane glycoprotein epithelial cell adhesion molecule (EpCAM) is overexpressed in most epithelial cancers including breast cancer, where it plays an important role in cancer progression. Previous study has demonstrated that knockdown of EpCAM inhibits breast cancer cell growth and metastasis via inhibition of the Ras/Raf/ERK signaling pathway and matrix metallopeptidase‐9 (MMP‐9). Although glycosylation is believed to be associated with the function of EpCAM, the contribution of N‐glycosylation to this function remains unclear. We constructed the N‐glycosylation mutation plasmid of EpCAM and used it to treat breast cancer cells. Loss of N‐glycosylation at all three sites EpCAM had no effect on its level of expression or membrane localization. However, mutation at glycosylation sites significantly reduced the ability of EpCAM to promote epithelial to mesenchymal transition in breast cancer. N‐glycosylation mutation of EpCAM led to decrease phosphorylation of Raf, ERK, and Akt, and inhibited the Ras/Raf/ERK and PI3K/Akt signaling pathways. Furthermore, we demonstrated that N‐glycosylation mutation of EpCAM‐mediated invasion and metastasis of breast carcinoma cells required the downregulation of MMP‐9 via inhibition of these two signaling pathways. Our results identified the characteristics and function of EpCAM glycosylation. These data could illuminate molecular regulation of EpCAM by glycosylation and promote our understanding of the application of glycosylated EpCAM as a target for breast cancer therapy. Abstract : N‐glycosylation in epithelial cell adhesion molecule affected epithelial to mesenchymal transition in breast cancer cells